The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.5539/ass.v11n1p187
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of the Training of Technical College Students Using Practice-Oriented Tasks

Abstract: Physics and chemistry are the comprehensive basis for the training of a modern engineer. The most important type of learning activities for the students is to solve problems. The purpose of this paper is to generalize and systematize the experience of increasing the motivation of students of technical training areas for the study of fundamental scientific disciplines using practice-oriented tasks. We identified the following educational functions of teaching objectives: cognitive, developing, a feature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The use of practice-oriented tasks to increase engineering students' motivation in learning of fundamental scientific disciplines was systematized and summarized by Politsinsky and Demenkova (2015), and Filho et al (2016). Politsinsky and Demenkova (2015) concluded that a practice-oriented approach helps to increase of learning motivation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of practice-oriented tasks to increase engineering students' motivation in learning of fundamental scientific disciplines was systematized and summarized by Politsinsky and Demenkova (2015), and Filho et al (2016). Politsinsky and Demenkova (2015) concluded that a practice-oriented approach helps to increase of learning motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This happens mostly when the learning activities of students are structured on the basis of projects, because implementing projects in the context of production may require special competences, which are often acquired by weak students. A number of scholars in education emphasize the need for the practice-based learning in designing teaching and learning activities to train engineers [8], and teaching physics and chemistry [9].…”
Section: Psychologicalmentioning
confidence: 99%